The potential of low-intensity and online interventions for depression in low- and middle-income countries. (19th August 2016) - Bockting, C. L. H.; Williams, A. D.; Carswell, K.; Grech, A. E.
Abstract : The World Health Organization (WHO) reports that low- and middle-income countries (LMICs) are confronted with a serious 'mental health gap', indicating an enormous disparity between the number of individuals in need of mental health care and the availability of professionals to provide such care (WHO in 2010). Traditional forms of mental health services (i.e. face-to-face, individualised assessments and interventions) are therefore not feasible. We propose three strategies for addressing this mental health gap: delivery of evidence-based, low-intensity interventions by non-specialists, the use of transdiagnostic treatment protocols, and strategic deployment of technology to facilitate access and uptake. We urge researchers from all over the world to conduct feasibility studies and randomised controlled studies on the effect of low-intensity interventions and technology supported (e.g. online) interventions in LMICs, preferably using an active control condition as comparison, to ensure we disseminate effective treatments in LMICs.